Legal education in Asia: From imitation to innovation - HARDING, Andrew (Institutional Knowledge at Singapore Management University, 2017)
Legal Education in Asia: From Imitation to Innovation is a curated collection of case studies that critically examine how conventional "transplanted" approaches to legal education are, or are on the cusp of being, redesigned across East Asia.